Optimizing Milling Margins: Implementing Sell-or-Continue Decisions in Paddy Production in Moncongloe Lappara Village, Indonesia - Muh Rum; Hafidzh Fachmy Rum (Manunggal Halim Jaya, 2026)
This study aims to optimize profit margins for farming businesses in Moncongloe Lappara Village through a